Prediction of hypotension using perfusion index following spinal anesthesia in lower segment caesarean section - Pradhan, Akshay Prasad; Sharma, Achyut; Shrestha, Amir Babu; Gurung, Tara; Shrestha, Sangeeta; Basnet, Ujjwal; Thakur, Jay Prakash; Kumar, Mukesh (Nepal Journal of Obstetrics and Gynaecology, 2020)
N/A